2000
DOI: 10.1093/milmed/165.10.773
|View full text |Cite
|
Sign up to set email alerts
|

Changing Demographic Characteristics of Women Veterans: Results from a National Sample

Abstract: Women veterans are a small but growing percentage of the U.S. veteran population. There are some indications that, along with this increase, the characteristics and military experiences of younger women veterans differ considerably from those of older colleagues. Many of these characteristics are not well defined, but they could have implications for women's health care needs and health policy initiatives. Using the first sample drawn from the Department of Veterans Affairs' new National Registry of Women Vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…As would be anticipated in a cohort seeking mental health services, the rate of MST in the current sample (67%) was higher than the reported prevalence rate of 22% among the general population of women VA clinic users (Kimerling et al, 2007). Rates of substance use disorders and childhood sexual trauma observed in this sample were also higher than those reported for the general population of women veterans (Sadler et al, 2003;Stern et al, 2000) but still within the range of previous reports of treatment-seeking women veterans (Butterfield, McIntyre, Stechuchak, Nanda, & Bastian, 1998;Fontana & Rosenheck, 1998). Also as anticipated, and consistent with previous findings, MST was associated with high rates of childhood sexual trauma (Merrill et al, 1999;Sadler et al, 2003;Suris et al, 2004): Those with MST were more likely to have experienced all three subtypes of childhood sexual abuse (non-contact, contact without penetration, and contact with penetration).…”
Section: Discussioncontrasting
confidence: 63%
“…As would be anticipated in a cohort seeking mental health services, the rate of MST in the current sample (67%) was higher than the reported prevalence rate of 22% among the general population of women VA clinic users (Kimerling et al, 2007). Rates of substance use disorders and childhood sexual trauma observed in this sample were also higher than those reported for the general population of women veterans (Sadler et al, 2003;Stern et al, 2000) but still within the range of previous reports of treatment-seeking women veterans (Butterfield, McIntyre, Stechuchak, Nanda, & Bastian, 1998;Fontana & Rosenheck, 1998). Also as anticipated, and consistent with previous findings, MST was associated with high rates of childhood sexual trauma (Merrill et al, 1999;Sadler et al, 2003;Suris et al, 2004): Those with MST were more likely to have experienced all three subtypes of childhood sexual abuse (non-contact, contact without penetration, and contact with penetration).…”
Section: Discussioncontrasting
confidence: 63%
“…First, using the traditional patientlevel sociodemographic and health-related predictors of VA ambulatory care use, our findings are consistent with those described in prior research on women veterans' VA use. 7,11,14,34 Our further incorporation of gender-related, veteran-related, and health care system-level domains into the behavioral model framework demonstrates a broader range of factors that are influencing women veterans' health care decision making. Given the changing demographics of women veterans, 34 and the greater VA knowledge deficits and lower quality perceptions we found among younger women veterans, our findings provide key insights into the barriers women veterans are facing in accessing VA care, and provide a foundation for understanding and acting upon inaccurate perceptions and mutable system characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…12,39,40 Yet in a sample of New England VA health care providers, only a minority believed it important that VA medical facilities accommodate women veterans' child care responsibilities. 41 In a literature review examining predictors of VA health care utilization in women, we found only two (arising from a single study) that examined the impacts of having dependent children, 41,42 even though child care problems are a well described barrier for nonveteran women's access of health services.…”
Section: Discussionmentioning
confidence: 99%